CNS Meningiomas in Children and Adolescents - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A clinicopathological analysis of 87 cases of meningioma in children and adolescents age 5 months to 20 years (mean 14 years) is reported from the Armed Forces Institute of Pathology, Walter Reed Army Medical Center, Children's National Medical Center, George Washington University, Washington, DC; Uniformed University of Health Sciences, Bethesda, MD; and Catholic University of Korea, Seoul.